An Event Based Analysis of Stock Return and Political Uncertainty in Pakistan: Revisited - Audi, Marc; Sulehri, Fiaz Ahmad; Ali, Amjad; Al-Masri, Razan (International Journal of Economics and Financial Issues, 2022)
This study provides an exploration of the impact of political events on the Pakistan Stock Market using a larger data set. The stock market of Pakistan which is considered the top-performing market in the region has suffered as well as foreign investors are reluctant to invest in Pakistan stock markets due to uncertainty caused by political instability. Pakistan is struggling against many problems; political instability is a significant problem due to which the economic growth of the country is being hindered and the confidence of the investors has been shaken. A total of 66 political events were considered in the study out of which 33 events were coded as positive and the other 33 were deemed negative. The first-day abnormal return, five-day cumulative abnormal return, and ten-day cumulative return were calculated for all of the events. The political events were analyzed by segregating these into Pre-Musharraf, Musharraf, and Post-Musharraf eras and also on the bases of their category. This study finds evidence that political events affect the Pakistan Stock Exchange, but their impact is different considering the economic and political implications of these events. Certain events had a stronger impact on the stock market like the takeover of Musharraf, suspension of the chief justice, and assassination of Benazir Bhutto. Political events provided more consistent results where elections yield positive stock returns and selection of prime minster yields negative stock returns after elections. Overall, this study lays the foundation to make further explorations into the phenomenon of uncertainty caused by political events in relevance to stock markets in Pakistan.